2021
DOI: 10.3390/molecules26175347
|View full text |Cite
|
Sign up to set email alerts
|

Parthenin—A Sesquiterpene Lactone with Multifaceted Biological Activities: Insights and Prospects

Abstract: Parthenin, a sesquiterpene lactone of pseudoguaianolide type, is the representative secondary metabolite of the tropical weed Parthenium hysterophorus (Asteraceae). It accounts for a multitude of biological activities, including toxicity, allergenicity, allelopathy, and pharmacological aspects of the plant. Thus far, parthenin and its derivatives have been tested for chemotherapeutic abilities, medicinal properties, and herbicidal/pesticidal activities. However, due to the lack of toxicity–bioactivity relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…This class of phytochemical constituent of plants has been implicated to possess anti-trypanosomal activities against different strains of Trypanosoma species. 23,24 However, the present study did not isolate, quantify or characterize the STLs from the VLC sub-fractions responsible for the moderate cytostatic and strong anti-trypanosomal activities against human foreskin fibroblast and Trypanosoma brucei brucei respectively. To further confirm the consistency in the strong antitrypanosomal activity of the STL constituents of T. diversifolia,…”
Section: In Vitro Anti-tb Brucei and Cytotoxic Activitiesmentioning
confidence: 76%
See 2 more Smart Citations
“…This class of phytochemical constituent of plants has been implicated to possess anti-trypanosomal activities against different strains of Trypanosoma species. 23,24 However, the present study did not isolate, quantify or characterize the STLs from the VLC sub-fractions responsible for the moderate cytostatic and strong anti-trypanosomal activities against human foreskin fibroblast and Trypanosoma brucei brucei respectively. To further confirm the consistency in the strong antitrypanosomal activity of the STL constituents of T. diversifolia,…”
Section: In Vitro Anti-tb Brucei and Cytotoxic Activitiesmentioning
confidence: 76%
“…The efficacy of the STLs-rich extracts against AAT-causing animal trypanosomiasis complements several other pharmacological properties of T. diversifolia towards discovering potent phyto-molecules. [7][8][9][10][11][12][13][14][15][16][17][18][19]21,23,28 This study identified the abundance of STLs in the extract of T. diversifolia and examined their potential as a promising source of anti-trypanosomal leads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hysterophorus) by using it as a rich source of chemicals such as parthenin, a sesquiterpene lactone. Parthenin shows medicinal properties such as antileishmanial, anticancer, microbicidal, anti-inflammatory, antiviral, and trypanocidal activities. …”
Section: Introductionmentioning
confidence: 99%
“…Parthenin shows medicinal properties such as antileishmanial, anticancer, microbicidal, anti-inflammatory, antiviral, and trypanocidal activities. 36 38 …”
Section: Introductionmentioning
confidence: 99%